Modified Newton-Raphson Method to Tune Feedback Gains of Control System for Standing by Functional Neuromuscular Stimulation Following Spinal Cord Injury - Raviraj Nataraj; Musa L. Audu; Ronald J. Triolo (Applied Bionics and Biomechanics)
Background: Functional neuromuscular stimulation (FNS) can restore standing capabilities following spinal cord injury. Feedback control of these systems can optimize performance by reducing the required upper extremity support. However, tuning these control systems can be intensive and clinically inconvenient.